Tendinopathy in Athletes : an IOC Medical Commission Publication. - Woo, Savio L-Y (Encyclopaedia of Sports Medicine, v.12., 2008)
This concise volume in the Encyclopaedia of Sports Medicine series, published under the auspices of the International Olympic Committee, provides a dependable source of current knowledge available on tendinopathy and covers both the basic science and clinical aspects of the subject. Despite its high incidence, the precise etiopathogenesis and effective treatment of tendinopathy remain elusive. Tendinopathy in Athletes draws on the expertise of an international and prolific collection of contributors, both clinicians and scientists, who provide new insights into this specialized area. This book.